2017
DOI: 10.1007/s11218-017-9418-6
|View full text |Cite
|
Sign up to set email alerts
|

Four mediation models of teacher expectancy effects on students’ outcomes in mathematics and literacy

Abstract: The study tested 4 direct and 28 indirect teacher expectancy effects on students' results in the mathematics and literacy sections of the matriculation test, and their final marks in the 12th-grade mathematics and literacy class. The following were considered as mediators: student self-esteem, their self-expectancy, and time spent learning mathematics and literacy. The study involved 1374 first year college students. Conducted path analyses revealed: (1) the total teacher expectancy effects was the strongest f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…It should be emphasized that lower performance and more negative self-concept of the female students were largely determined by lower judgments of their capabilities. Similar results, in more recent studies, were obtained by Plante et al (2019), Rudman and Phelan (2010), Szumski and Karwowski (2019), and Trusz (2018).…”
Section: Students' Self-expectancies Concerning Typically Female and supporting
confidence: 91%
See 2 more Smart Citations
“…It should be emphasized that lower performance and more negative self-concept of the female students were largely determined by lower judgments of their capabilities. Similar results, in more recent studies, were obtained by Plante et al (2019), Rudman and Phelan (2010), Szumski and Karwowski (2019), and Trusz (2018).…”
Section: Students' Self-expectancies Concerning Typically Female and supporting
confidence: 91%
“…To sum up, interpersonal expectancy effects can be regulated by students' self-expectancies and self-concepts of abilities. The indicated factors connect the expectancies of significant others with students' achievement, and at the same time, directly influence their educational careers (Trusz 2018;Rubie-Davies 2006;Tosto et al 2016;Wigfield and Eccles 2000). Consequently, inter and intrapersonal stereotype-tinged expectancies may influence the results of the matriculation tests and subsequent selection of study majors made by females and males.…”
Section: Students' Self-expectancies Concerning Typically Female and mentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, the study carried out by Özer ve Korkmaz [38] showed that teacher's positive attitudes and behaviours, giving each student right to talk, making them feel that their teacher cares about themselves are of the factors influencing students' success in foreign language teaching. In another study the findings showed that the direct teacher expectancy effects were important and positive for mathematics and literacy test results [39]. Moreover, another result obtained from the study was about the influence of teacher expectancy on the students' attitudes and students' success.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 87%
“…Similarly, the study carried out by Özer and Korkmaz [41] showed that teachers' positive attitudes and behaviors, giving each student the right to talk, and making them feel that their teacher cared about them, are the factors that influence students' success in foreign language learning. In another study, the findings showed that direct teacher expectancy effects had significant and positive effects on mathematics and literacy test results [42].…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 95%